ANALISIS PENDAPATAN USAHATANI PADI SAWAH (Oryza sativa L) DI DESA KAUDITAN 1 KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Richard Christianto Katiandagho; Paulus A. Pangemanan; Tommy F. Lolowang (Sam Ratulangi University, 2018)
This research aims to analyzed income of rice paddy farmers. This research conducted in Kauditan 1 village north Minahasa Regency from june to july 2018. The method used survey method by visiting rice paddy farming. Data collection method in this research using primary data. Primay data obtained from interview with rice paddy farmers using questionnaires, and secondary data from related agency statistic center bureau north Minahasa Regency. The sampling all rice paddy farmers, 5 respondent. Variable in this research is characteristic of farming: land area, land tenure status, seeds, fertilizers, medicine and characteristic of farmer: age, education level, family member, fixed cost, variable cost, total cost, price, production quantity. Data presented in the table form and analyzed descriptively. The result showed that average income of rice paddy farmers Rp.31,849,420 and average income based on land area Rp.18,780,342 with R/C ratio more than 1,2.47.*lwths*.